Effectiveness of Audit and Feedback and Academic Detailing Interventions to Support Safer Opioid Prescribing in Primary Care - Lacroix, Meagan; Abdelmalek, Fred; Everett, Karl; Taljaard, Monica; Salach, Lena; Bevan, Lindsay; Burton, Victoria; Jia, Hui; Shuldiner, Jennifer; Laur, Celia; Angl, Emily Nicholas; Ivers, Noah M; et al. (The American journal of medicine, 2025)
Opioids, prescribed to manage pain, are associated with safety risks. Quality improvement strategies such as audit and feedback and academic detailing may improve prescribing in primary care. We used a matched-cohort design with claims databases. Participants were family physicians practicing in Ontario, Canada. The interventions were a voluntary audit and feedback report with or without academic detailing sessions. Physicians in the control group received neither intervention. The primary outcome was mean rate of high-risk opioid prescriptions per 100 patients per month. Data were analyzed comparing monthly percentage change in slope over 12 months before and 18 months after the intervention. Additional analyses considered only the subgroup of higher-prescribing physicians. There were 1469 (25%) physicians in the audit and feedback group, 245 (4%) in the audit and feedback + academic detailing group, and 4211 (71%) matched controls. All groups showed a significant preintervention decline in opioid prescribing. There were no significant between-group differences in opioid prescribing postintervention. Among high-prescribing physicians, there was a significant reduction in the audit and feedback group (% change in slope = -0.37, 95% CI = -0.65 to -0.09, P < .01), but not in the academic detailing group (% change in slope = 0.19, 95% CI = -0.52 to 0.91, P = .59). This study demonstrated declining secular trends in prescribing and suggests that two large-scale initiatives had limited additional benefits. We found some additional reductions after audit and feedback among the highest-volume opioid prescribers. Future interventions should focus on these physicians for the greatest benefit.